Megathrust and accretionary wedge properties and behaviour in the Makran subduction zone. Issue 3 (23rd March 2017) - Penney, Camilla; Tavakoli, Farokh; Saadat, Abdolreza; Nankali, Hamid Reza; Sedighi, Morteza; Khorrami, Fateme; Sobouti, Farhad; Rafi, Zahid; Copley, Alex; Jackson, James; Priestley, Keith
Summary: We study the Makran subduction zone, along the southern coasts of Iran and Pakistan, to gain insights into the kinematics and dynamics of accretionary prism deformation. By combining techniques from seismology, geodesy and geomorphology, we are able to put constraints on the shape of the subduction interface and the style of strain across the prism. We also address the long-standing tectonic problem of how the right-lateral shear taken up by strike-slip faulting in the Sistan Suture Zone in eastern Iran is accommodated at the zone's southern end. We find that the subduction interface in the western Makran may be locked, accumulating elastic strain, and move in megathrust earthquakes. Such earthquakes, and associated tsunamis, present a significant hazard to populations around the Arabian Sea. The time-dependent strain within the accretionary prism, resulting from the megathrust earthquake cycle, may play an important role in the deformation of the Makran region. By considering the kinematics of the 2013 Balochistan and Minab earthquakes, we infer that the local gravitational and far-field compressive forces in the Makran accretionary prism are in balance. This force balance allows us to calculate the mean shear stress and effective coefficient of friction on the Makran megathrust, which we find to be 5–35 MPa and 0.01–0.03, respectively. These values are similar to those found in other subduction zones, showing that the abnormally high sediment thickness in the offshore Makran does not significantly reduce the shear stress on the megathrust.